ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN PROGRAM BELAJAR PADA LEMBAGA BIMBINGAN BELAJAR BES KEDIRI - Siti Qurotul Aini; Mundir Mundir; Riza Faishol; Ana Aniati; Alfiyah Darojat (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Facing the era of globalization filled with competition, education becomes a prerequisite for participating in future development. This has led to the emergence of many tutoring institutions, resulting in intense competition in the education service industry. The aim of this research is to develop a new learning program strategy using the SWOT analysis method at BES Kediri Tutoring Institution. The results of the SWOT analysis for the next period need to enhance the quality of learning, improve English language courses and Conversational skills not offered by other tutoring institutions, and enhance learning services that are equal to or better than competitors. Based on the SWOT quadrant matrix analysis, it is concluded that BES tutoring institution has a total strength greater than weaknesses, while total opportunities are smaller than threats. Therefore, BES tutoring institution falls into quadrant II. The strategy formulated is diversification strategy (product/market) efforts to seek and develop new products or markets, or diversify to expand market share or all of the above.